Factors associated with knowledge and awareness of HIV/AIDS among married women in Bangladesh: evidence from a nationally representative survey - Md. Ashiqul Haque; Md. Sha Newaj Hossain; Muhammad Abdul Baker Chowdhury; Md. Jamal Uddin (Taylor & Francis Group, 2018)
Women in Bangladesh share a greater risk of Human Immunodeficiency Virus (HIV)/Acquired Immune Deficiency Syndrome (AIDS) infection compared to men. Levels of knowledge and awareness largely contribute to the prevalence of the HIV epidemic and its consequences. So, it is required to conduct studies based on most recent data to explore the determinants of HIV awareness. Therefore, we aimed to find the awareness level and factors influencing HIV related awareness among the married women in Bangladesh. We used data from 2014 Bangladesh Demographic and Health Survey (BDHS). About two-third of total respondents who heard about the HIV/AIDS were selected and interviewed successfully (n = 12,593) about 11 basic questions related to individual's awareness. A score of the respondent's knowledge and awareness was determined based on these questions. We used logistic regression models for analysing the data. We found about 62% of the respondents had an adequate knowledge and consciousness about the HIV/AIDS. Respondents' education status, mass-media access, place of living, and working status played significant role on the awareness. As expected, respondents with higher education were more aware than those with no education (odds ratio (OR) = 3.56, 95% confidence interval (CI): 2.99-4.23). Moreover, respondents who had access to the mass media were more likely to be aware compared to those who did not have the access (OR = 1.14, 95% CI: 1.04-1.26). Although a sizeable proportion of women had an adequate knowledge and awareness regarding the HIV/AIDS, we recommend implementing educational programmes related to HIV/AIDS in the curriculum to ensure a standard level of awareness throughout the nation. Since the respondents from rural areas scored significantly lower than the urban areas, awareness through mass media, particularly in rural areas, is of prime concern for raising awareness.